רעיונות סגפניים וארוחות: תעצומות הגוף והנפש ריטואליות בכתביו של ר’ בחייה בר אשר - אפטרמן אדם; פינטו עידן (מחשבת ישראל, 2021)
This article examines asceticism in the writings of R. Baḥya Ben Asher ibn Ḥalawa from Saragossa (1255–1340), through a study of two Halakhic practices of fasting and feasting. The first part of the article analyzes Baḥya’s perceptions of fasting, engaging with its effects on the relationship between body and soul, and more specifically on the inner relations between the different faculties of the soul. The ritual of fasting is thus portrayed as focused on the human soul, not on the body, ultimately leading to the ascension and empowerment of the intellectual soul over the animalistic one. The second part of the article is devoted to a study of ritualistic meals in Baḥya’s writings. This study revolves around Baḥya’s interpretation of the two biblical feasts: Isaac’s feast before his death (Gen. 27:4) and Jethro’s feast celebrating his conversion (Ex. 18:12), which serve as models for halakhically mandated celebratory meals. Here Baḥya relied on the interesting interpretation of his teacher R. Solomon b. Aderet’s (known as Rashba) – to which he added the mystical element of the drawing down of the Holy Spirit. Additionally, the article examines related topics such as Baḥya’s critical view of the status of fasting among Christians and Muslims, his perception of the relationship between fasting and feasting, as well as his attitude toward joy, the heavenly eating of Adam before the fall, and vegetarianism.